2017
DOI: 10.1021/acs.biomac.7b00673
|View full text |Cite
|
Sign up to set email alerts
|

Constructing an Anisotropic Triple-Pass Tubular Framework within a Lyophilized Porous Gelatin Scaffold Using Dexamethasone-Loaded Functionalized Whatman Paper To Reinforce Its Mechanical Strength and Promote Osteogenesis

Abstract: In bone tissue engineering (BTE), most of the currently developed scaffolds still lack the ability to demonstrate high porosity and high mechanical strength simultaneously or the ability to maintain bioactivity and sustained release of loaded biofactors. In this work, we constructed an anisotropic triple-pass tubular framework within a lyophilized porous GEL scaffold using FP, which was prepared by coating DEX-covered Whatman paper (WP) using the silk fibroin (SF) membrane with β-sheet conformation. This novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Compressive strength increased significantly when β‐TCP was contained within the scaffold: the scaffold with 20% β‐TCP (G80T20) had a compressive strength 9.4 times that of the scaffold without β‐TCP nanoparticles (gelatin). Note that the compressive strengths of all composite scaffolds containing β‐TCP were in the range of cancellous bone (2–20 MPa); [ 23,24 ] this indicates that the G80T20, G60T40, and G40T60 scaffolds can support newly formed tissue in the implantation site. [ 25 ] As a result, we concluded that all scaffolds with β‐TCP particles have suitable mechanical properties for bone tissue regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Compressive strength increased significantly when β‐TCP was contained within the scaffold: the scaffold with 20% β‐TCP (G80T20) had a compressive strength 9.4 times that of the scaffold without β‐TCP nanoparticles (gelatin). Note that the compressive strengths of all composite scaffolds containing β‐TCP were in the range of cancellous bone (2–20 MPa); [ 23,24 ] this indicates that the G80T20, G60T40, and G40T60 scaffolds can support newly formed tissue in the implantation site. [ 25 ] As a result, we concluded that all scaffolds with β‐TCP particles have suitable mechanical properties for bone tissue regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…30,45 Similar results were reported in other studies where adding silicate nanoparticles to polymer signicantly improved the mechanical strength of the nanocomposite lms. 46,47 It should be noted that despite the compressive strength of the prepared scaffolds didn't reach the standard of cancellous bone (2-20 MPa), 48,49 the fabricated GC-Lap scaffolds can still be applied in non-load bearing bone defect repair. Moreover, once implanted in vivo, the compressive strength of the porous scaffolds increased with the ingrowth of new bone tissue.…”
Section: Mechanical Testingmentioning
confidence: 99%